Assessment of Dental Age Estimation Using Aspartic Acid Racemization in Human Dentin in Single-Rooted Teeth - Neelima Dasarathi; Kiran Kumar Kattappagari; Venkata Suresh Ponnuru; Ravi Teja Chitturi Suryaprakash; Arvind Babu Santhosh; Baddam Venkat Ramana Reddy (Journal of Orofacial Sciences, 2022)
Introduction: Dental age estimation has always been a very important and very susceptible subject in forensic science, as it is an essential requirement in living, dead human individual’s remains. Aspartic acid racemization is considered to be one of the advanced, reliable, accurate, and complex biochemical methods. There will be an amendment of Levo aspartic acid to dexto aspartic acid when the age advances. To estimate the dental age of single-rooted teeth using aspartic acid racemization. Material and Methods: Thirty anterior teeth were collected from maxillary and mandibular arches distributed into four groups. All teeth were analyzed for Levo (l) and Dextro (d) form of aspartic acid using a high-performance liquid chromatography technique and the ratio of amino acid racemization for each sample was determined. The obtained data were subjected to step-wise linear regression analysis for the ratio of d and l aspartic acid against actual age with estimated age. Results: Distribution of teeth about age maximum samples was collected at 51 to 60 years. l-aspartic acid ratio was more in the younger age group but when the age increases d-aspartic acid ratio was increased. Linear regression analysis showed maximum samples showed very close to the actual age (30%). Conclusion: By analyzing the levels of aspartic acid using amino acid racemization, we can estimate an individual with maximum accuracy. Accretion of d-aspartic acid in dentin is synchronous with the aging of an individual and this method can be used as one of the precise methods for dental age estimation.